Formation of sustainable development competencies in primary school children - Levchyk, Iryna; Chaikovska, Hanna; Yankovych, Oleksandra; Kuzma, Iryna; Rozhko-Pavlyshyn, Tetiana (Journal of Education Culture and Society, 2021)
Aim. The article provides a new solution to the problem of the formation of sustainable development competencies in primary school students. The objective of the article is to substantiate the method of forming sustainable development competencies in primary school students and to reflect it in the model. Methods. The main research methods are observation, test, interview, questionnaire, analysis of media works, expert evaluation, and pedagogical experiment. A set of diagnostic tools has been specified. Results and Conclusions. The efficiency of the developed technique has been proved with the results obtained from the experiment: the partnership of teachers, students and parents contributes to sustainability competencies formation; implementation of common areas of media education and education for sustainable development evidenced to feasibility of the research, namely: education in legal, economic aspects, creation of media products with a projection to sustainable development, learning critical perception of mass media information, sustainability goals orientation. Due to the introduction of the experimental methodology, the number of students with high (12.07%) and satisfactory (14.65%) levels of the key competencies in the field of sustainable development increased against the background of a decrease in the number of respondents with sufficient (12.93%) and low (13.79%) levels. Originality. Emphasis is placed on the features of the designed methodology: application of partnership pedagogy and pedagogy of empowerment, integration of education for sustainable development with media education, compliance with a number of pedagogical conditions, forms and methods.